PENGARUH ENTERPRISE RISK MANAGEMENT TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABLE MEDIASI PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BEI PERIODE 2019-2021 - Yohana Monica S.; Lorina Siregar Sudjiman (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research was conducted with the aim of analyzing and finding out how Enterprise Risk Management influences company value in insurance sub-sector companies listed on the IDX for the 2019-2021 period. The sampling technique was carried out by purposive sampling, 15 companies were selected from 18 companies for 3 years with a total sample of 45 companies. The source of data in this study is secondary data downloaded through the official IDX website. The type of research used is descriptive analysis method and the type of research is quantitative research. The data analysis technique in this study used multiple linear regression analysis. Data processing uses SPSS and through several analyzes, namely descriptive test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, T test, F test, and determination test. The results of this study indicate that Enterprise Risk Management simultaneously has a significant effect on company value in insurance sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period.